Controlled release of lysozyme from double-walled poly(Lactide-Co-Glycolide) (PLGA) microspheres - Ansary, Rezaul H.; Rahman, Mohd. Mokhlesur; Mohamad, Nasir A.N.; Arrif, Tengku M; Abdul Latif, Ahmad Zubaidi; Katas, Haliza; Wan Nik, Wan Sani; Awang, Mohamed (MDPI AG, 2017)
Double-walled microspheres based on poly(lactide-co-glycolide) (PLGA) are potential delivery systems for reducing a very high initial burst release of encapsulated protein and peptide drugs. In this study, double-walled microspheres made of glucose core, hydroxyl-terminated poly(lactide-co-glycolide) (Glu-PLGA), and carboxyl-terminated PLGA were fabricated using a modified water-in-oil-in-oil-in-water (w1/o/o/w2) emulsion solvent evaporation technique for the controlled release of a model protein, lysozyme. Microspheres size, morphology, encapsulation efficiency, lysozyme in vitro release profiles, bioactivity, and structural integrity, were evaluated. Scanning electron microscopy (SEM) images revealed that double-walled microspheres comprising of Glu-PLGA and PLGA with a mass ratio of 1:1 have a spherical shape and smooth surfaces. A statistically significant increase in the encapsulation efficiency (82.52 ± 3.28%) was achieved when 1% (w/v) polyvinyl alcohol (PVA) and 2.5% (w/v) trehalose were incorporated in the internal and external aqueous phase, respectively, during emulsification. Double-walled microspheres prepared together with excipients (PVA and trehalose) showed a better control release of lysozyme. The released lysozyme was fully bioactive, and its structural integrity was slightly affected during microspheres fabrication and in vitro release studies. Therefore, double-walled microspheres made of Glu-PLGA and PLGA together with excipients (PVA and trehalose) provide a controlled and sustained release for lysozyme.